The dialectics of historical empathy as a reflection of historical thinking in South African classrooms (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The research explores the understanding of the concept Historical empathy as conceptualised by the two teachers sampled in this study. The article analyses the pedagogical practices of two Grade 12 History teachers who used the theme of the Vietnam War of 1954 to 1975, also known as the Second Indochina War, and in Vietnam as the Resistance War Against America or simply the American War, was a conflict that occurred in Vietnam, Laos, and Cambodia from 1 November 1955 to the fall of Saigon on 30 April 1975. This is one of the new themes included in the Curriculum and Assessment Policy Statement (CAPS) to cultivate tenets of Historical empathy in their classrooms. The research utilises a qualitative research paradigm to enable the researchers to interview teachers at their schools and observe them interacting with the phenomenon being investigated in their natural environment in the classrooms. The article uses the dual theoretical framework designed by Barton and Levstik (2004) which embodies both elements of affective and cognitive domains to evaluate the perspectives of two teachers and their pedagogical practices in the classroom. According to the findings, both teachers used suitable and relevant primary and secondary sources during the lesson presentations. Teachers demonstrated characteristics of emotional and cognitive empathy during the interviews and these divergent elements were displayed during the teaching of the Vietnam War. Quite often learners were encouraged by one teacher to sympathise and align with the victims of the war which is caused by their past agony and psychological trauma resulting from the experiences of their communities during the apartheid government and this demonstrated shared normalcy. The second teacher empathised with the Vietnamese soldiers and saw them as gallant soldiers against the strong US troops rather than as victims thereby displaying some elements of cognitive Historical empathy.
Keywords: Historical empathy; Presentism; Historical contextualisation; Normalcy; Sense of otherness; Multi-perspectivity